2004
DOI: 10.1007/s00122-004-1706-9
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions influencing resistance to the parasitic weed Striga hermonthica in two recombinant inbred populations of sorghum

Abstract: Molecular markers for resistance of sorghum to the hemi-parasitic weed Striga hermonthica were mapped in two recombinant inbred populations (RIP-1, and -2) of F(3:5) lines developed from the crosses IS9830 x E36-1 (1) and N13 x E36-1 (2). The resistant parental lines were IS9830 and N13; the former is characterized by a low stimulation of striga seed germination, the latter by "mechanical" resistance. The genetic maps of RIP-1 and RIP-2 spanned 1,498 cM and 1,599 cM, respectively, with 137 and 157 markers dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 40 publications
(41 reference statements)
4
135
0
1
Order By: Relevance
“…These accessions may be useful potential sources of resistance to Striga as such or in a backcross breeding program. It would be interesting to confirm whether the mechanical type of Striga resistance that has been mapped using Quantitative Trait Loci (QTL) and reported elsewhere [10] would be found in genotypes with low stimulants production. In order to consolidate this resistance, these accessions of low stimulant production could be crossed with the already identified backcrosses with intro-gressed Striga resistance QTL from a previous study [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These accessions may be useful potential sources of resistance to Striga as such or in a backcross breeding program. It would be interesting to confirm whether the mechanical type of Striga resistance that has been mapped using Quantitative Trait Loci (QTL) and reported elsewhere [10] would be found in genotypes with low stimulants production. In order to consolidate this resistance, these accessions of low stimulant production could be crossed with the already identified backcrosses with intro-gressed Striga resistance QTL from a previous study [6].…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms of resistance to Striga in sorghum have been reported that probably operate singly or in various combinations [9] [10]. Using in-vitro laboratory techniques, four specific mechanisms of resistance to Striga which included low production of germination stimulant, low production of the haustoria initiation factor, hypersensi-tive response, and incompatible response were reported in cultivated sorghums and some wild accessions [5] [11].…”
Section: Introductionmentioning
confidence: 99%
“…QTL mapping for Striga resistance has resulted in identification of many genes/QTLs spread across the genome. Haussmann et al (2004) mapped several QTLs for Striga resistance in sorghum and reported 9 and 11 QTLs explaining respectively 77% and 82% of the phenotypic variation in a recombinant inbred line (RIL) population. The most significant QTL has been identified to correspond to the major gene locus lgs, which was recently fine-mapped on the chromosome 5 (Satish et al, 2012).…”
Section: Marker-assisted Selectionmentioning
confidence: 99%
“…The invention of molecular markers has enhanced the effectiveness of breeding for resistance. Five genomic regions (QTLs) with linked markers associated with Striga resistance were mapped in sorghum variety N13 by [10]. In this study, to increase the efficiency of marker-assisted selection (MAS), 27 EST-SSR markers in close association with Striga resistance QTLs were also identified and mapped.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, five QTLs underlying different Striga resistant phenotypes and molecular SSR markers associated with specific region have been identified and assigned to their specific chromosomal location [10]. These regions and associated SSR markers have been used in advanced backcross populations allowing exploitation of diverse resistance sources [20].…”
Section: Introductionmentioning
confidence: 99%